Rapid and remarkable effectiveness of benralizumab for treating severe bronchial asthma with intractable eosinophilic rhinosinusitis and eosinophilic otitis media: A case report. (2021) - Shimizu, Hideyasu; Kato, Hisayuki; Yoshioka, Satoshi; Okazawa, Mitsushi
Abstract: Severe bronchial asthma is a challenging disorder to treat and can impair quality of life (QOL) under conventional therapeutic modalities. We report the case of a 52-year-old woman with severe asthma associated with eosinophilic chronic rhinosinusitis (ECRS) and eosinophilic otitis media (EOM). Although the patient was treated with a full dose of inhaled corticosteroid, leukotriene receptor antagonist (LTRA), theophylline, burst use of oral corticosteroids (OCS), her asthmatic condition aggravated, disrupting her daily life. ECRS and EOM symptoms were also getting worse despite treatment with topical application of corticosteroids to the nose and ears, LTRA, and occasional use of OCS. In addition to asthmatic symptom, the patient always suffered from intractable nasal obstruction and hearing disturbance, which contributed to the heavily impaired QOL. However, the administration of benralizumab showed rapid and remarkable improvement not only in her asthmatic conditions but also in the symptoms of ECRS and EOM within a month. These results suggest that the use of benralizumab for the treatment of severe asthma with intractable ECRS and EOM should be considered when the patient's QOL is severely deteriorated.